E3. Maternal haemodynamics follow-up after pregnancies complicated by HDP and/or IUGR. (12th August 2016) - Di Martino, D.; Zullino, S.; Casati, D.; Grimaldi, A. S.; Mastroianni, C.; Sterpi, V.; Rosti, E.; Garbin, M.; Ferrazzid, E.
Abstract: Aims : To compare maternal hemodynamic profile during pregnancy and at 6–12 months after delivery in pregnancies with different HDP phenotypes or severe IUGR. Methods : We enrolled patients between 24 and 38 weeks of gestation: HDP with appropriate for gestational age foetuses (HDP-AGAf), HDP with IUGR (HDP-IUGR), severe IUGR and Controls matched for gestational age. Severe IUGR was defined as abdominal circumference <5th centile and a PI in umbilical artery42SD. Diagnosis of HDP was made according to the criteria of the ISSHP. Maternal echocardiography was performed during pregnancy and at 6–12 months after delivery to compare in each group cardiac output (CO), total vascular resistance (TVR) and tissue Doppler E'/A' wave ratio. Results : Maternal heart rate and CO were reduced and TVR increased during pregnancy, and did not change significantly at follow-up in the 10 HDP-IUGR and in the 8 severe IUGR recruited. Heart rate, CO and TVR in the 8 HDP-AGAf were similar to Controls both during pregnancy and at follow-up except for a significantly increased MAP and a reduced E'/A' ratio. Discussion : Maternal hemodynamic changes at 6–12 months postpartum varies according to different physio-pathological phenotypes of maternal HDP and placental damage.